ENGINEERING EDUCATION IN THE SOUTHERN FEDERAL UNIVERSITY: RESULTS AND PROSPECTS - Igor A. Kalyayev; Viktor V. Petrov (Высшее образование в России)
The article gives an assessment of the current state of engineering education development in the Southern Federal University (SFEDU) and considers its prospects. The authors discuss the foundation of the Engineering and Technological Academy that now includes all the relevant educational and research departments of SFEDU. The main purpose of the Engineering and Technological Academy is integration of education, science and production in a single educational research and innovative center, as well as the development of the system of engineers training to meet the new realities and challenges of technical progress.